Online Learning in Pandemic: The Level of Stress And Satisfaction of Pre-Service Teachers - Marilyn P. Coronel; Nurfaiza Joe; Crizy Jane Quililan; Kayesha V. Amabao; Lea Mae M. Garces (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The outbreak of a deadly virus called Corona has prompted schools and colleges to switch instruction from face-to-face to online learning (Masha'al et al., 2020). Even with no records nor archives of online teaching-learning, imperative steps were implemented to counterbalance the educational institutions brought by the global outbreak (Joe et al., 2022). Because of its versatility, young learners across the world mainly in more developed countries opted for an online learning (Handang, 2022). Normal classrooms have been replaced by e-classrooms quickly, implying that students and teachers have adjusted. According to Carey (2020) the challenges present are not how online teaching and learning methodologies can give excellent education rather on how schools can adjust to online learning in giving quality education. Digital learning reflects a vastly distinct educational setting where learners already can study from a variety of online materials in addition to those accessible in the classroom (Saldariega et al., 2022).